Finding out fast about the impact of COVID-19: The need for policy-relevant methodological innovation - Rahman, Hossain Zillur; Matin, Imran; Banks, Nicola; Hulme, David (Elsevier, 2022)
This article was published in World Depelopment [©2021 Published by Elsevier Ltd. All rights reserved.] and the definite version is available at: https://doi.org/10.1016/j.worlddev.2020.105380 The Article's website is at: https://www.sciencedirect.com/science/article/pii/S0305750X20305088#!